Mouth Cancer: the Maxillofacial Surgeon's perspective. (2nd November 2020) - Goodson, Alexander MC; Parmar, Satyesh; Praveen, Prav; Idle, Matthew; Martin, Timothy
Abstract : This article summarizes current practice according to UK guidelines for the management of oral cancer from the perspective of the oral and maxillofacial surgeon. The article discusses the patient pathway, starting with recognition of sinister features by the general dental practitioner in primary care and referral to specialist oral and maxillofacial surgery services, followed by the multidisciplinary approach to tumour staging, cancer treatment planning and delivery, and finally key issues in the 'post-treatment' phase of cancer care. Additional focus is provided for some of the surgical treatments and anatomical and physiological changes, of which the general dental practitioner should have some understanding. CPD/Clinical Relevance: General dental practitioners play a key role in the detection and early management of oral cancer, referring approximately 40% of all cases to secondary care. It is therefore important to understand key milestones and technical elements of the patient's journey.